Coping with Depopulation and Demographic Ageing in Rural Japan: From Government to Local Governance - Doo-Chul, Kim; Hye-Jin, Bu (Journal for Geography, 2009)
Recently, the Japanese government initiated an administrative process that has resulted in the merging of municipalities across the country. Since then, the quality of services provided to inhabitants by the local government has declined in depopulated areas. As a result, it has been suggested that there may be a role for self-organization in the revival of local governance. Despite having a rapidly ageing population, Kawane village has been particularly successful in revitalizing local governance through reorganization of the local community. This research examines a variety of the community activities involved and the unique management methods behind them in an attempt to ascertain the factors that have resulted in successful selfgovernance in this village.